Penggunaan Aksis Jantung Pisang untuk Penyediaan Sumber Eksplan Bebas Bakteri - Ika Roostika; Yati Supriyati; Agus Sutanto (Jurnal AgroBiogen, 2015)
The sterile culture is very important in cryopreservation works. Bacterial-free explant sources are difficult to obtain during invitro culture of banana. Floral bud is expected as bacterial-free explant sources because the organ emerges above the groundand protected by bracts. The purposes of this study are to obtain optimal concentration of BA to regenerate male bud floralaxis explants of Barangan variety and to prove that cultures derived from these explants were free from bacterialcontamination. Two-millimeter pieces of male bud floral axis of Barangan variety were planted on MS medium containing of 1μM IAA, 200 g/l CH, and 2% sucrose. Experiment was arranged in Completely Randomized Design with the treatment of BA (5,10, 15, 20, and 25 μM) in 10 replications. Subculture was conducted by using MS media containing of 10 μM BA and 1 μM IAA.The variable observed were percentage of browning, number of nodules, number of shoots, number of normal shoots,number of abnormal shoots, and number of nonsurvived shoots. The screening towards bacterial contamination wasconducted by using medium containing of 10 g/l trypton, 10 g/l glucose, and 5 g/l yeast extract. The results showed that theexplants could regenerate into shoots. The 25 μM BA was the best treatment because it could produce the highest number oftotal and normal shoots, i.e. 9.2 shoots/explant and 6 shoots/explant, respectively. All of the shoots regenerated from male budfloral axis were 100% free from bacterial contamination, whereas all of the shoots regenerated from suckers werecontaminated by bacteria.